Gender Education in the Family (The Urgent Parenting of Gender Equality in Early Childhood) - Mardliyah, Layla (International Conference of Moslem Society, 2018)
This paper focuses on primary family education about parenting of gender equality in early childhood. Parenting of gender equality in early childhood is nurturing through gender education in the family that is undertaken to develop the abilities covering the cognitive, affective and psychomotor aspects of the children. The main thing is to build a children’s sensitivity during the interaction with their social environment. Based on the research findings, the construction of community in Sokaraja believed that the children were a valuable asset to be cared for with love and affection. This required the role and responsibility of parents to provide education to their children; as evidence of children who were as the pride and grace provided by God. Unfortunately, during the education process, there was gender bias happened to children to become unequal in terms of the responsibility and the roles between boy and girl. Gender bias made the children sensitive to the differences and responsibilities. The children were treated in different ways, thus it could generate the feelings of injustice to the children. The construction of understanding within the family eventually influenced the society at large, partly in the school environment. In fact, religious elites often contributed to this gender bias. Therefore, in line with the deconstruction toward the understanding of gender bias, the children needed to be raised in a family environment that had parenting of gender equality so that the children could have sensitivity and responsibility to themselves and his environment. The children’s behavior in the future would depend on the treatment and parenting in the family.